ANALISIS DISPARITAS KEMISKINAN DI PROVINSI JAWA TIMUR TAHUN 2015-2024: PENDEKATAN INDEKS WILLIAMSON: POVERTY DISPARITY ANALYSIS IN EAST JAVA PROVINCE 2015-2024: WILLIAMSON INDEX APPROACH - A'yunin Hafidhatul Ilmi; nurul Lathifah (Universitas Negeri Surabaya, 2025)
Poverty is a complex and multidimensional problem. This is due to its interconnectedness with various aspects, including social, economic, cultural, and other aspects. East Java as the second most populous region in Indonesia faces poverty issues. This study aims to analyze the level of poverty disparity between districts/cities in East Java Province for the period 2015–2024 using the Williamson Index approach. The data used are the percentage of the poor population and the total population from the official publication of the Central Statistics Agency (BPS). The research method used is descriptive quantitative with the calculation of the Williamson Index to measure inequality between regions. The results show that the value of the Williamson Index for East Java is in the range of 0.38–0.41, which is categorized as moderate inequality. This increase indicates that poverty reduction is not fully evenly distributed across the province, especially between urban areas such as Surabaya, Sidoarjo, and Malang which have advanced economic sectors and rural areas such as Madura and Tapal Kuda which are still structurally lagging.